The Urgence of Legal Policy to Fulfill The Constitutional Rights to Employment Social Security for Vulnerable Workers in The National Social Security System - Rudiansyah Putra (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: The problems studied in this thesis are regarding legal policy from the point of view of the prevailing regulations in indonesia, especially those relating to the fulfillment of constitutional rights. Employment social security for workers and the urgency of fulfillment of social security rights for workers of vulnerable groups who are unable to pay contributions. The research method used is juridical-normative research using an approach that synchronizes the applicable legal provisions in the legal protection of norms or other legal regulations with their relation to the application of legal regulations in practice in the field. The result of the study is that there is a conflict between article 14 paragraph (1) of uu. No. 40 of 2004 concerning the national social security system and the mandate of the 1945 constitution. Social security only targets workers who are wage earners and those who are able to pay contributions, but vulnerable workers are not protected under the social security. Keywords: Urgency; social security; vulnerable workers.